Construction and validation of a mammalian expression vector for in utero electroporation study of miR-3099 in the mouse neocortex - Zainal Abidin, Shahidee; Lee, Han Chung; Fam, Sze Zheng; Abdullah, Syahril; Nordin, Norshariza; Cheah, Pike See; Ling, King Hwa (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2018)
Introduction: MiR-3099 was reported to play a role in neuronal cell differentiation/function in the brain during late embryonic and early neonatal development. To further explore its potential regulatory effects on embryonic brain development, this study aims to construct and validate an expression vector of miR-3099 for future gain-of-function and loss-of-function studies. Methods: pCAG-eGFP vector was modified to include IRES2 and miR-3099 with 150bp upstream and downstream genomic sequences. The newly constructed vector, pCAG-miR-3099-IRES2-eGFP, consists of CAG promoter. The in vitro expression level of miR-3099 was measured using stem-loop RT-qPCR after it was transfected into 293FT cell. Later, the vector was electroporated into the embryonic brain at E15.5. Three days later, the E18.5 embryonic brain was harvested and cryopreserved. Immunohistochemistry was performed by using antibody against eGFP to validate the in utero expression of the transgene in the neocortex of the brain. Results: Our finding showed that, the expression level of miR-3099 was significantly upregulated (p<0.001) in cells transfected with miR-3099 vector as compared to both negative and empty plasmid control groups. In addition, the expression of eGFP was noted in the brain section indicating that the vectors with or without miR-3099 transgene were successfully transfected into and expressed in the neocortex upon electroporation. Conclusion: The bicistronic expression vector of miR-3099 which was driven by the CAG promoter was successfully constructed, validated and sufficiently delivered to brain cells via the in utero electroporation approach. The regulatory roles of miR-3099 in embryonic brain development can be manipulated using similar approach.